Geology of guapiara topographic sheet in 1:50.000. - Vieira, Otávio Augusto Ruiz Paccola [UNESP]; Godoy, Antonio Misson [UNESP]; Hackspacher, Peter Cristian [UNESP]; Leite Junior, Washington Barbosa [UNESP] (My University, 2018)
Geology of Guapiara Topographic Sheet in 1:50.000. The region of Guapiara Topographic Sheet is located in the extreme South of the São Paulo state and it is comprised in the central portion of the Mantiqueira Province in the South-central zone of the Ribeira Belt. The local geological framework involves rocks from the metavulcanic sedimentary sequence of the Açunguí Supergroup, Meso– to Neoproterozoic age, deformed and metamorphosed in the Neoproterozoic, associated with granitoid rocks generated during the collisional episodes related to the Brasilian Cycle and to the Gondwana Supercontinent formation. The main lithostratigraphic units are composed of the Água Clara Formation and the Votuverava and Itaiacoca groups metassediments of Mesoproterozoic age, Neoproterozoic granite bodies representing the Três Córregos Granite and the Capão Bonito Granite, Itararé Group sedimentary rocks, associated intrusive rocks of the Serra Geral Magmatism and recent Quaternary sediments. The structural-metamorphic framework is determined by the Neoproterozoic final tectonic arrangement, evidenced in the epimetamorphic rocks by a polyphase structural evolution, with four deformation phases (Sn, Sn+1, Sn+2 e Sn+3) and three metamorphic events (M1, M2 and M3) of a regional progressive, contact and regional to locally dynamic of a retrometamorphic nature feature, respectively.
Geologia da folha topográfica guapiara na escala 1:50.000.
Keywords: Geological mapping; Geology; Guapiara; Structural analysis